PENGARUH SITUS JEJARING SOSIAL FACEBOOK SEBAGAI MEDIA ALTERNATIF UNTUK PROMOSI - Agus Triyono (JURNAL DIAN, 2011)
Social networking site Facebook has been growing very rapidly in lndonesia. lts presence gives agreat impact in establishing communication with the broader community.This site can be an alternative choice for the promotion and building a profitable business through online channels.One is the product oriflame that specializes beauty products forboth men and women,household and other needs are secondary lifestyle. This site is a media community that attracted many mothers, young women and men to develop its business. Through this networking productscan be offered with great ease so that more people can easilyaccess it. The response was so great from facebookers, contributing huge that its products will be easy to understand,understood and exploited its function properly.Keyword : Facebook, Media,Promotion